Certified Kubernetes Administrator (CKA) Study Guide - Muschko, Benjamin (O'Reilly Media, Inc., 2022)
The ability to administer and monitor a Kubernetes cluster is in high demand today. To meet this need, the Cloud Native Computing Foundation developed a certification exam to establish a system administrator's credibility and value in the job market to confidently work in a Kubernetes environment. The Certified Kubernetes Administrator (CKA) certification exam is different from the typical multiple-choice format of other professional certifications. Instead, the CKA is a performance-based exam that requires deep knowledge of the tasks under immense time pressure. This study guide walks you through all the topics covered to fully prepare you for the exam. Author Benjamin Muschko also shares his personal experience with preparing for all aspects of the exam. Learn when and how to apply Kubernetes concepts to administrate a production-grade cluster Understand the objectives, abilities, and tips and tricks needed to pass the CKA exam Explore the ins and outs of the kubectl command-line tool Demonstrate competency to perform the responsibilities of a Kubernetes system administrator Solve real-world Kubernetes problems in a hands-on command-line environment Effectively navigate and solve questions during the CKA exam.